2018
DOI: 10.1007/s10815-018-1315-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and transplantation of ovarian tissue: results from one center in the USA

Abstract: PurposeTo report the results of cryopreserved ovary tissue transplantation for leukemia and other cancers, in a single US center.MethodsOne hundred eight females between age 6 and (median age 24) 35 were referred for possible ovary tissue cryopreservation over a 20-year period, with either slow freeze or vitrification. Thus far 13 patients returned up to 18 years later to have their tissue transplanted back.ResultsAll 13 patients had return of ovarian function 5 months post transplant with regular menstrual cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 63 publications
3
78
0
Order By: Relevance
“…34 Recently, live births have been achieved after transplantation of cryopreserved ovarian tissue that had been harvested after inducing the remission of leukemia, following sufficient assessment for minimal residual disease, and there has been no recurrence in any cases up to now. [37][38][39] The same safety issues have also been raised in ovarian tissue transplantation in ovarian malignancies such as borderline ovarian tumors (BOTs) or early stage of patients with ovarian cancer, as they are also candidates for fertility preservation. 40,41 Masciangelo et al 40 analyzed frozen-thawed and xenografted ovarian tissue from 11 patients with BOT.…”
Section: Risk Of Reintroducing Malignant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Recently, live births have been achieved after transplantation of cryopreserved ovarian tissue that had been harvested after inducing the remission of leukemia, following sufficient assessment for minimal residual disease, and there has been no recurrence in any cases up to now. [37][38][39] The same safety issues have also been raised in ovarian tissue transplantation in ovarian malignancies such as borderline ovarian tumors (BOTs) or early stage of patients with ovarian cancer, as they are also candidates for fertility preservation. 40,41 Masciangelo et al 40 analyzed frozen-thawed and xenografted ovarian tissue from 11 patients with BOT.…”
Section: Risk Of Reintroducing Malignant Cellsmentioning
confidence: 99%
“…34 Recently, live births have been achieved after transplantation of cryopreserved ovarian tissue that had been harvested after inducing the remission of leukemia, following sufficient assessment for minimal residual disease, and there has been no recurrence in any cases up to now. 37-39…”
Section: Risk Of Reintroducing Malignant Cellsmentioning
confidence: 99%
“…This procedure leads to restoration of ovarian activity in more than 95% of cases (Donnez et al 2015). Transplantation of cryopreserved ovarian tissue has been steadily increasing all over the world and more than 130 live births have been reported to date, yielding live birth rates in the range of 23-77% (Donnez et al 2015, Meirow et al 2016, Van Der Ven et al 2016, Donnez & Dolmans 2017, Jensen et al 2017, Diaz-Garcia et al 2018, Silber et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen ovarian tissue may be thawed followed by auto-transplanted upon completion or treated with in vitro maturation of oocytes. Previous studies have confirmed return of ovarian function and live births after transplanting the cryopreserved tissue [41,42]. If women requiring chemotherapy wish to omit cryopreservation, gonadotropin releasing hormone agonists (GnRHa) have shown some efficacy in preventing treatment induced POI [43].…”
Section: Ovarian Failurementioning
confidence: 99%